A Linguistics Investigation of Grammatical Errors by Maithili ESL Learners Through Error Analysis - Singh, Anchal; Astha, Astha; Thakur, Isha Satyanand; Krishna, Devina (Vivid: Journal of Language and Literature, 2023)
The purpose of the paper is to present how the interference of an individual's mother tongue hinders in acquiring a second language, which leads to Interlingual errors. It is an observation that the speakers also commit those errors which have no influence of the mother tongue but are a result of the target language which are called Intralingual errors. This paper particularly focuses on how the Maithili language (LI) acts as a hindrance for the Maithili ESL learners to acquire the target language, that is, the English language (L2). The survey also displays the traces of Intralingual errors in the responses of the speakers, who are committing grammatical errors in speaking the English language (L2). The analysis and evaluation of the results that have been procured through the digital questionnaire survey conducted has been displayed in this paper. The general survey shows that people admitted making grammatical errors while speaking both native and second language and it can be inferred from the specific survey that the same respondents have committed errors in more than half of the questions given to them. The objective of the paper is not only to show the various reasons which lead the Maithili ESL speakers to commit errors while speaking or writing the English language but also to profuse remedies to overcome these barriers. It can be concluded from the entire research that the hypothesis is justified and there is a scope for remedial measures to correct the situation.